2023
DOI: 10.3390/vaccines11121810
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Nucleocapsid-Targeting Vaccines against COVID-19

Alexandra Rak,
Irina Isakova-Sivak,
Larisa Rudenko

Abstract: The new SARS-CoV-2 coronavirus, which emerged in late 2019, is a highly variable causative agent of COVID-19, a contagious respiratory disease with potentially severe complications. Vaccination is considered the most effective measure to prevent the spread and complications of this infection. Spike (S) protein-based vaccines were very successful in preventing COVID-19 caused by the ancestral SARS-CoV-2 strain; however, their efficacy was significantly reduced when coronavirus variants antigenically different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 104 publications
1
0
0
1
Order By: Relevance
“…Initial mouse studies with our mRNA vaccines have shown that mRNA-N is highly immunogenic and induces strong N-specific binding antibody and T cell (both CD4 + and CD8 + ) responses, despite there being no neutralizing antibodies. Although only modest effects were achieved, mRNA-N vaccination did protect the mouse and hamster from mouse-adapted SARS-CoV-2 and VOCs, respectively [5,16]. Critically, our study also showed that combined mRNA-N and mRNA-S immunization (mRNA-S+N) protected against Delta and Omicron infection in hamsters, whereas mRNA-S alone only induced mild protection [5].…”
Section: Introductionsupporting
confidence: 48%
“…Initial mouse studies with our mRNA vaccines have shown that mRNA-N is highly immunogenic and induces strong N-specific binding antibody and T cell (both CD4 + and CD8 + ) responses, despite there being no neutralizing antibodies. Although only modest effects were achieved, mRNA-N vaccination did protect the mouse and hamster from mouse-adapted SARS-CoV-2 and VOCs, respectively [5,16]. Critically, our study also showed that combined mRNA-N and mRNA-S immunization (mRNA-S+N) protected against Delta and Omicron infection in hamsters, whereas mRNA-S alone only induced mild protection [5].…”
Section: Introductionsupporting
confidence: 48%
“…В качестве анализируемых объектов рассмотрены фрагменты символьных последовательностей, ассоциированных с тремя различными штаммами вируса SARS-CoV-2 (ковида) -«Ухань», «Дельта» и «Омикрон». Вирус SARS-CoV-2 продолжает представлять высокую потенциальную угрозу для человечества [20] вследствие своей высокой антигенной изменчивости [21]. Среди генов, кодирующих белки SARS-CoV-2, значительный интерес для исследований представляет спайк-ликопротеин, или S-белок, оказывающий влияние на проникновение вируса в клетки хозяина [22,23].…”
Section: Introductionunclassified